Karakteristik Sensori dan Fisikokimia Biskuit Berbahan Baku Tepung Kacang Merah dan Tepung Ubi Jalar Ungu - Ghania, Rizka; Yanti, Rini; Manikharda, Manikharda (Jurnal Teknologi Hasil Pertanian, 2024)
Modified biscuits are made from purple sweet potato flour to reduce dependence on wheat flour. In addition, red bean flour (Phaseolus angularis) was added to increase the nutritional value of the biscuits. This study aimed to determine the effect of different ratios of purple sweet potato flour and red bean flour on the physical, chemical, and organoleptic characteristics of biscuits and their benefits as alternative foods to meet the nutritional needs of stunted toddlers. Various formulations of biscuits consisted of four formulations based on the ratio of red bean to purple sweet potato flour. They were P1 ( 70%:30%), P2 (50%:50%), P3 (30%:70%) dan control (0%: 100%). The biscuit acceptability test for four biscuit formulations (P1, P2, P3, and P4) was carried out using the hedonic test. The selected formula was determined based on the preferences of 68 untrained panelists. The results showed that P2 biscuits containing 50% red bean flour and 50% purple sweet potato flour were the best formulas. It had a moisture content of 4.58% db, ash of 2.74% db, fat of 30.33% db, protein 6 .78 %db, carbohydrates by difference 60.15 %db, total energy 540.72 kcal/100g; physical values: color L*= 31.47, a* =14.13, b*= 13.52, hardness 11.73 N; The overall acceptance test for liking is 4.97 (somewhat like). Biscuits contain 4 grams of protein/serving, where the formula can meet 20% of a child's protein needs per day from 17 pieces of biscuits or the equivalent of 58.91 grams of biscuits.